Primary Gastrointestinal T/NK Cell Lymphoma - Kim, Eun Kyung (Cancers (Basel), 2021)
SIMPLE SUMMARY: Primary gastrointestinal T/NK cell lymphoma (GI-TNKL) is a heterogeneous group including various subtypes, anatomic locations, and clinicopathologic features. GI-TNKL is difficult to diagnose due to its rarity, various subtypes, and histopathological features. We performed a retrospective analysis of 38 cases of GI-TNKL in South Korea. GI-TNKL consisted of unique subtypes showing specific characteristics of macroscopy, histology, immunophenotype, and prevalent anatomic subsites. ENKTL and MEITL were relatively common. GI-TNKL showed aggressive behavior with short PFS and OS. This clinical and pathological descriptive analysis will be helpful for accurate understanding, diagnosis, and treatment. ABSTRACT: Primary gastrointestinal T/NK cell lymphoma (GI-TNKL) is an uncommon and heterogeneous group of lymphoid malignancies. We aimed to investigate their subtype distribution, clinicopathologic characteristics, and clinical outcomes. A total of 38 GI-TNKL cases and their clinical and pathological characteristics were analyzed. GI-TNKL occurred in adults with a median patient age in the sixth decade of life and showed a slight male predominance. The most common histologic type was extranodal NK/T-cell lymphoma, nasal type (ENKTL; 34.2%), followed by monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL; 31.6%), intestinal T-cell lymphoma, NOS (ITCL, NOS, 18.4%), anaplastic large cell lymphoma, ALK-negative (ALCL, ALK-; 13.2%). The small intestine was the primary affected region. More than 90% of patients complained of various GI symptoms and cases with advanced Lugano stage, high IPI score, or bowel perforation that required emergent operation were not uncommon. GI-TNKL also showed aggressive behavior with short progression-free survival and overall survival. This thorough clinical and pathological descriptive analysis will be helpful for accurate understanding, diagnosis, and treatment.